A data-driven contrastive study on Malay ESL learners’ use of lexical verbs and verb-noun collocations in argumentative writing / Shazila Abdullah - Abdullah, Shazila (2015)
Learner writing is often characterized by linguistic errors, especially in lexical verbs, which can contribute to communicative incompetence. It is also generally known that verb-noun collocations are a characteristic of native writing. The main objective of this thesis is to investigate the linguistic errors made by non-native learners and to suggest ways how they can improve their level of proficiency. Previous studies have looked into the occurrences of either lexical verbs or verb-noun collocations with little emphasis on the phraseology of verb-noun collocations formed from commonly used lexical verbs. Based on these premises, the thesis explores the use of lexical verbs and verb-noun collocations in two learner corpora, one of which is a native learner corpus and the other a specific group of non-native learners, i.e. Malay ESL learners. The data-driven analysis specifically adopted for this study allows for a focus on the most commonly used lexical verbs and verb-noun collocations. Furthermore, an in-depth contrastive interlingual analysis between the corpora of native and non-native learners enables the researcher to uncover the difficulties that learners face in using these lexical items. The meticulous processes involved in compiling the non-native learner corpus and the extraction of verb-noun collocations add to the uniqueness of the thesis. The thesis addresses three main questions through a linguistic analysis using both quantitative and qualitative methods with the assistance of WordSmith Tools. First, it seeks to examine linguistic elements of the lexical verbs; second, to ascertain the phraseological patterns of verb-noun collocations; and third, to identify the non-native elements found in the use of lexical verbs and verb-noun collocations. The results reveal some similarities and differences that help in understanding how lexical verbs and verb-noun collocations are actually used by both native and non-native learners in writing. What is most obvious is the Malay ESL learners' lack of vocabulary repertoire, which indicates a lack of vocabulary acquisition. The analysis of verb-noun collocations reveals an array of phraseological deviations that stem from a lack of knowledge in syntagmatic relationships between the two lexical elements in the collocations. It is, thus, essential for learners to learn how to use a variety of lexical verbs, including the lexical patterns and grammatical patterns of verb-noun collocations in order to use them appropriately, especially when these patterns differ from their L1. A framework on learning and teaching of the lexical verbs and verb-noun collocations has been proposed based on the findings. This framework can contribute to the improvement of an English syllabus, material design and teaching methodology. It is hoped that the most important contribution of this thesis is to increase awareness of the importance of phraseology in ELT so that various measures can be taken to enhance learners' communicative competence, which should be the aim of every English course.